CONFLICT OF SHADOW STATION EXISTENCE (Case Study in Jatibening Shadow Station) - Nicea Regalia Lovea AM; Yuwanto . (Journal of Politic and Government Studies, 2018)
The existence of shadow station is a phenomenon that appears as a form of policy that made by the user community. Shadow stations appear in several locations which according to the user community are strategic locations. Jatibening Shadow Station located in the toll road area of ex Pondok Gede Timur. Its existence facilitates the needs of the community, but violates the existing rules. This caused a conflict between PT. Jasa Marga as the toll road manager and the community around the station. Conflict of the existence of Jatibening Shadow Station has purpose to knowing how to resolve conflicts and the results of existing conflicts resolution, as well as knowing the appearance of the Jatibening Shadow Station itself.This study uses a type of descriptive research with a qualitative approach. Qualitative approaches use structured interview techniques, field observations, and document review. Document review is used by adding data from books, scientific papers, and articles from the internet that support research.Activities at Jatibening Shadow Station have been going on for a long time. The results showed that the main cause of the community's rejection of the total closure of Jatibening Shadow Station was its very strategic location being the main attraction of the Jatibening Shadow Station. Its existence also helps the economy of the surrounding community. PT. Jasa Marga want to restore the function of the toll road in accordance with existing regulations triggers different conflicts of interest. Compromise was taken as a middle ground in resolving conflicts over the existence of Jatibening Shadow Station. The compromise taken resulted in a letter of agreement between the two parties. The shadow terminal continues to operate with a lay bay.Keywords : Shadow Station, Conflict, Conflict Resolution, Good Governance